2016
DOI: 10.1016/j.drugalcdep.2016.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of nicotine dependence among adolescent waterpipe smokers

Abstract: Introduction Waterpipe smoking is addictive and its use is increasing globally among youth, yet little is known about the factors associated with nicotine dependence (ND) among waterpipe smokers. We investigated the factors associated with ND symptoms among a sample of Lebanese adolescents who smoke a waterpipe. Methods We collected data on factors potentially associated with ND (individual, socio-demographic, environmental, smoking patterns) among 160 current (past 30 days) waterpipe smokers recruited from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 60 publications
(107 reference statements)
2
32
0
Order By: Relevance
“…Six psychological factors were assessed: stress (Cronbach’s ‘α’=0.79), depressive symptoms (α=0.75), novelty seeking (α=0.76), impulsivity (α=0.81), self-esteem (α=0.79) and distractibility (α=0.63) 21. Baseline waterpipe use frequency (less than weekly, weekly but not daily, daily), number of waterpipes (ie, heads) smoked in the past 30 days, and the usual length of a smoking session (<30 min, 30–60 min, >60 min) were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six psychological factors were assessed: stress (Cronbach’s ‘α’=0.79), depressive symptoms (α=0.75), novelty seeking (α=0.76), impulsivity (α=0.81), self-esteem (α=0.79) and distractibility (α=0.63) 21. Baseline waterpipe use frequency (less than weekly, weekly but not daily, daily), number of waterpipes (ie, heads) smoked in the past 30 days, and the usual length of a smoking session (<30 min, 30–60 min, >60 min) were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…A cut-off value of VIF ≤5 was applied to rule out multicollinearity 21. Accordingly, multicollinearity was not an issue in this analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Department of Health and Human Services 2014), and that less frequent use is less likely to be associated with ND among adolescents (O'Loughlin et al 2003). More details about the WDLY study can be found elsewhere (Bahelah et al 2016a). …”
Section: Methodsmentioning
confidence: 99%
“…Using interviewer-administered questionnaires, participants provided information about their tobacco use patterns and responded to measures of ND (Bahelah et al 2016a; DiFranza et al 2007). Interviewers met participants individually in private rooms on school premises and school personnel were not allowed during interviews to minimize social-desirability bias.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation